The Fourth Battalion Duke of Connaught's Own Tenth Baluch Regiment in the Great War. - Thatcher, W. S. (Luton : Andrews UK, 2011)
The part played by Indian soldiers in the Great War is, as the author of this excellent and excitingly written history correctly complains, somewhat under-appreciated. He blames this on the fact that Regular Army officers in Indian Regiments were too few and too over-worked to write down the essntial facts, while the Indians themselves did not write in English. For W.S. Thatcher, a volunteer who joined up at the outbreak of the war 'for the duration' - his service with the Baluchis remained ...
Cover; Contents; Front Matter; Half Title; Frontispiece; Title Page; Title Page Verso; Dedication; Preface; Quotes; Body Matter; Chapter I; Chapter II; Chapter III; Chapter IV; Chapter V; Chapter VI; Chapter VII; Chapter VIII; Chapter IX; Chapter X; Chapter XI; Chapter XII; Chapter XIII; Chapter XIV; Chapter XV; Chapter XVI; Chapter XVII; Back Matter; Appendix I; Appendix II; Appendix III; Appendix IV; Appendix V; Appendix VI; Appendix VII; Appendix VIII; Appendix IX; Index.
Print version record.
eBooks on EBSCOhost
Keywords: Great Britain. -- Army. -- 4/10th Baluch Regiment (Duke of Connaught's Own); World War, 1914-1918 -- Regimental histories -- Great Britain; Guerre mondiale, 1914-1918 -- Histoire des unités -- Grande-Bretagne.; HISTORY -- Military -- World War I; Regimental histories; Great Britain; 1914-1918